Protocol-Driven Enteral Nutrition in Critically Ill Children: A Systematic Review. (January 2014) - Wong, Judith Ju-Ming; Ong, Chengsi; Han, Wee Meng; Lee, Jan Hau
Enteral nutrition (EN) protocols are thought to improve clinical outcomes in the pediatric intensive care unit (PICU); however, critical evaluation of their efficacy is limited. We conducted a systematic review with the aim of assessing the effect of EN protocols on important clinical outcomes in these children. We searched MEDLINE, Cochrane Database for Reviews, Embase, and CINAHL using predetermined keywords and MESH terms. We included randomized controlled trials (RCTs) and observational studies that involved EN protocols in children admitted to the PICU for >24 hours. We included studies that reported at least 1 of our outcomes of interest. Studies that exclusively studied premature neonates or adults were excluded. Primary outcomes were PICU or hospital mortality, PICU or hospital length of stay (LOS), duration of mechanical ventilation, gastrointestinal (GI) complications, and infective complications. Secondary outcomes were time to initiate feeds and time to achieve goal feeds. In total, we included 9 studies (total 1564 children) in our systematic review (1 RCT, 4 before-and-after studies, 1 single-arm cohort study, 1 prospective descriptive study, and 2 audits). There is low-level evidence that the use of EN protocols is associated with a reduction in GI and infective complications and improved timeliness of feed initiation and achievement of goal feeds. Current medical literature does not have compelling data on the effects of an EN protocol on clinical outcomes among critically ill children. Future clinical trials should look into using standardized interventions and outcome measures to strengthen the existing evidence.